2021
DOI: 10.21037/jtd-20-2826
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognostic analysis of metastatic pulmonary sarcomatoid carcinoma: a SEER analysis

Abstract: Background: Pulmonary sarcomatoid carcinoma (PSC) is a rare type of non-small cell lung cancer (NSCLC). Metastases are often detected at the first diagnosis. Despite high rates of distant metastasis, there is insufficient data describing the characteristics of PSC metastasis.Methods: We performed a Surveillance, Epidemiology, and End Results (SEER) database-based analysis of clinicopathological features and prognosis of distant metastasis in PSC patients. Data queried for this analysis included PSC patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…A large-scale retrospective analysis of pulmonary sarcomatoid carcinoma conducted by Xiao et al., via the SEER database, found that the proportion of pulmonary sarcomatoid carcinoma was only 0.5% of lung cancer worldwide ( 10 ).In this current study, the 55 patients with pulmonary sarcomatoid carcinoma accounted for only 0.16% of the patients diagnosed with lung cancer during the same period, which was slightly lower than that reported by Li et al. ( 11 14 ).…”
Section: Discussioncontrasting
confidence: 66%
“…A large-scale retrospective analysis of pulmonary sarcomatoid carcinoma conducted by Xiao et al., via the SEER database, found that the proportion of pulmonary sarcomatoid carcinoma was only 0.5% of lung cancer worldwide ( 10 ).In this current study, the 55 patients with pulmonary sarcomatoid carcinoma accounted for only 0.16% of the patients diagnosed with lung cancer during the same period, which was slightly lower than that reported by Li et al. ( 11 14 ).…”
Section: Discussioncontrasting
confidence: 66%
“…Pleomorphic carcinoma of the lung is a relatively rare pathologic diagnosis that accounts for approximately 0.1–0.4% of non-small cell lung cancer [ 5 ]. The prognosis of pleomorphic carcinoma has been reported to be worse than adenocarcinoma or squamous cell carcinoma [ 6 ] because of the aggressive tumor progression, including distant organ metastasis [ 7 ]. Any type of non-small cell lung carcinoma can metastasize to distant organs, including the GI tract; however, a study has shown that pleomorphic carcinomas are significantly associated with GI tract metastasis than other types of non-small cell lung carcinomas [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3] It has a more aggressive clinical course and a poorer response to chemotherapy than other forms of lung malignant tumors. [4,5] Our case showed intestinal bleeding due to small intestinal metastasis of pulmonary pleomorphic carcinoma, although intestinal bleeding is not a very common initial sign of recurrence of resected lung malignant tumors. It was reported that 11.9% of lung cancer patients had gastrointestinal metastases according to an autopsy analysis.…”
Section: Discussionmentioning
confidence: 73%
“…[ 3 ] It has a more aggressive clinical course and a poorer response to chemotherapy than other forms of lung malignant tumors. [ 4 , 5 ]…”
Section: Discussionmentioning
confidence: 99%